Development of GAVIAMORIDA E-Booklet based on Diversity of Gastropods and Bivalves Research at Mangrove Morosari Demak as Alternative Source of Learning - Romadhoni, Mar`atush Sholihah; Widiyaningrum, Priyantini; Susanti, R. (Journal of Innovative Science Education, 2021)
The Mangrove Morosari Demak was once a densely populated area, but due to the abrasion process of the Java Sea, the area was eventually submerged. This condition affects the survival of Gastropods and Bivalves. This study aims to develop an e-booklet based on the research of Gastropods and Bivalves’ Diversity in the Mangrove Morosari Demak. The e-booklet is named GAVIAMORIDA which stands for Gastropods and Bivalves in the Mangrove Morosari Demak. This development research uses the ADDIE method with 5 stages: Analyse, Design, Develop, Implement and Evaluate. This research resulted a kind of e-booklet “GAVIAMORIDA” with detailed information about 11 types of Gastropods and 1 Bivalves which found in the Mangrove Morosari Demak. The average value of diversity index (H ') is 2.116 (moderate), evenness index (E) is 0.912 (high), and dominance index (C) is 0.131 (stable). The results of the validation from two kinds validators (experts and users) were 85.61% which were classified as "very valid" and "Feasible to produce with revisions according to suggestions". The results of the effectiveness of the GAVIAMORIDA e-booklet showed a high N-Gain value of 0.73. The conclusion of this study is the GAVIAMORIDA e-booklet feasible and effective as an alternative source of learning for high school students.